2020
DOI: 10.1038/s41598-020-67746-4
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-terminal hydrolase L1 (UCHL1) regulates post-myocardial infarction cardiac fibrosis through glucose-regulated protein of 78 kDa (GRP78)

Abstract: Abnormal cardiac fibrosis indicates cardiac dysfunction and poor prognosis in myocardial infarction (MI) patients. Many studies have demonstrated that the ubiquitin proteasome system (UPS) plays a significant role in the pathogenesis of fibrosis. Ubiquitin C-terminal hydrolase L1 (UCHL1), a member of the UPS, is related to fibrosis in several heart diseases. However, whether UCHL1 regulates cardiac fibrosis following MI has yet to be determined. In the present study, we found that UCHL1 was dramatically increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
1
30
1
Order By: Relevance
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus. Genes such as KCNE5 [ 45 ], SHANK3 [ 46 ], CASQ2 [ 47 ], EDNRA (endothelin receptor type A) [ 48 ], EPHB4 [ 49 ], ALPK3 [ 50 ], WNT11 [ 51 ], IRAK2 [ 52 ], FBN1 [ 53 ], SFRP2 [ 54 ], CLCA2 [ 55 ], NEXN (nexilin F-actin binding protein) [ 56 ], PALLD (palladin, cytoskeletal associated protein) [ 57 ], DAB2 [ 58 ], NRP2 [ 59 ], THBS2 [ 60 ], CSF1R [ 61 ], KCNA2 [ 62 ], CACNA1C [ 63 ], F2R [ 64 ], UCHL1 [ 65 ], CCL18 [ 66 ], ITGB1BP2 [ 67 ] and FMOD (fibromodulin) [ 68 ] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [ 69 ], Liu et al [ 70 ], Eltokhi et al [ 71 ], Cai et al [ 72 ], Pfeiffer et al [ 73 ], Lin et al [ 74 ], Royer-Zemmour et al [ 75 ], Pastor et al [ 76 ], Goodspeed et al [ 77 ], Zhang et al [ 78 ], Rogers et al [ 79 ], Su et al [ 80 ] and Foale et al [ 81 ] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were the genes expressed in progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus. Genes such as KCNE5 [ 45 ], SHANK3 [ 46 ], CASQ2 [ 47 ], EDNRA (endothelin receptor type A) [ 48 ], EPHB4 [ 49 ], ALPK3 [ 50 ], WNT11 [ 51 ], IRAK2 [ 52 ], FBN1 [ 53 ], SFRP2 [ 54 ], CLCA2 [ 55 ], NEXN (nexilin F-actin binding protein) [ 56 ], PALLD (palladin, cytoskeletal associated protein) [ 57 ], DAB2 [ 58 ], NRP2 [ 59 ], THBS2 [ 60 ], CSF1R [ 61 ], KCNA2 [ 62 ], CACNA1C [ 63 ], F2R [ 64 ], UCHL1 [ 65 ], CCL18 [ 66 ], ITGB1BP2 [ 67 ] and FMOD (fibromodulin) [ 68 ] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [ 69 ], Liu et al [ 70 ], Eltokhi et al [ 71 ], Cai et al [ 72 ], Pfeiffer et al [ 73 ], Lin et al [ 74 ], Royer-Zemmour et al [ 75 ], Pastor et al [ 76 ], Goodspeed et al [ 77 ], Zhang et al [ 78 ], Rogers et al [ 79 ], Su et al [ 80 ] and Foale et al [ 81 ] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were the genes expressed in progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the legumain-mediated degradation is related to non-lysosomal proteolysis, such as the UPS which is present in all eukaryotic cells and is believed to be responsible for non-lysosomal proteolysis 44 and thus could modulate the remodelling of ECM after MI 45 , 46 . We thus checked the expression of E3 ubiquitin ligase—a key enzyme in ubiquitination that promotes protein ubiquitination and degradation in the cardiac tissue post-MI—and found that E3 expression was increased in the cardiac tissue post-MI; however, E3 expression was not affected by RR-11a treatment (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus genes and advancement. KCNE5 [45], SHANK3 [46], CASQ2 [47], EDNRA (endothelin receptor type A) [48], EPHB4 [49], ALPK3 [50], WNT11 [51], IRAK2 [52], FBN1 [53], SFRP2 [54], CLCA2 [55], NEXN (nexilin F-actin binding protein) [56], PALLD (palladin, cytoskeletal associated protein) [57], DAB2 [58], NRP2 [59], THBS2 [60], CSF1R [61], KCNA2 [62], CACNA1C [63], F2R [64], UCHL1 [65], CCL18 [66], ITGB1BP2 [67] and FMOD ( bromodulin) [68] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [69], Liu et al [70], Eltokhi et al [71], Cai et al [72], Pfeiffer et al [73], Lin et al [74], Royer-Zemmour et al [75], Pastor et al [76], Goodspeed et al [77], Zhang et al [78], Rogers et al [79], Su et al [80] and Foale et al [81] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were linked with progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%